The 1947 Constitution and the nationalities - Kyo'Van'; Takkasuil my a Samuin Sutesana Thana (Rangoon, Burma) (Yangon : Universities Historical Research Centre, and Innwa Pub. House, 1999)
Politics in Burma, 1885-1948, and the 1947 Constitution
Bibliography : p. 272-284
Keywords: Constitutional history -- Burma; Burma -- Politics and government -- 1824-1948